Os desafios da educação de jovens e adultos no meio rural em Breves-Marajó Pará - BORGES, Vitória Rodrigues (2024)
The present study aims to carry out a bibliographical study on the challenges of youth and adult education in rural areas in Breves-Marajó-Pará. The aim is to highlight the specificities of EJA, making a brief historical outline, from the beginning to the present day, of Youth and Adult Education, going through what the legislation currently provides for the modality. And from that, taking a look at the role of EJA in Rural Education, noting the absence of EJA in the BNCC, and from this, the importance of having a curriculum adapted to the modality and that has relevance, relationship and meanings for the reality of rural/riverside school students who access the modality, in order to discuss the challenges to guarantee Youth and Adult Education in rural/riverside communities.